FROM PODCASTS TO DOCUMENTARIES: EXPLORING AUTHENTIC MATERIALS FOR ENHANCED LISTENING SKILLS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Annotation. The present research explores the various types of authentic materials and their significant contribution towards the development of listening skills of the students. Authentic materials such as podcasts, video recordings, music compositions, radio shows, and everyday conversations expose learners to language in its natural context, hence promoting better listening skills and all-round language proficiency. The research uses real-life examples, statistical findings, student ratings, and theoretical concepts as corroborating evidence for the use of authentic materials in the context of learning the language of English.